2008
DOI: 10.1158/0008-5472.can-08-1691
|View full text |Cite
|
Sign up to set email alerts
|

Routine Diagnostic X-ray Examinations and Increased Frequency of Chromosome Translocations among U.S. Radiologic Technologists

Abstract: The U.S. population has nearly one radiographic examination per person per year, and concern about cancer risks associated with medical radiation has increased. Radiologic technologists were surveyed to determine whether their personal cumulative exposure to diagnostic X-rays was associated with increased frequencies of chromosome translocations, an established radiation biomarker and possible intermediary suggesting increased cancer risk. Within a large cohort of U.S. radiologic technologists, 150 provided a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The initial decline may be due at least in part to the co-occurrence of reciprocal translocations with unstable forms of chromosome damage (Tucker 2008). Recent studies of radiologic technologists have observed increased frequencies of chromosome aberrations in this cohort occupationally exposed to radiation (Bhatti et al 2007(Bhatti et al , 2008Sigurdson et al 2008a). These studies suggest that chromosome aberrations, particularly reciprocal translocations, hold promise as a biomarker of both exposure and cancer risk, but numerous concerns about potential confounding due to factors such as age, cigarette smoking, and phenotypic differences remain (Sigurdson et al 2008b;Tucker 2008).…”
Section: Does Error-prone Dna Repair Results In An Increase In Risk?mentioning
confidence: 80%
“…The initial decline may be due at least in part to the co-occurrence of reciprocal translocations with unstable forms of chromosome damage (Tucker 2008). Recent studies of radiologic technologists have observed increased frequencies of chromosome aberrations in this cohort occupationally exposed to radiation (Bhatti et al 2007(Bhatti et al , 2008Sigurdson et al 2008a). These studies suggest that chromosome aberrations, particularly reciprocal translocations, hold promise as a biomarker of both exposure and cancer risk, but numerous concerns about potential confounding due to factors such as age, cigarette smoking, and phenotypic differences remain (Sigurdson et al 2008b;Tucker 2008).…”
Section: Does Error-prone Dna Repair Results In An Increase In Risk?mentioning
confidence: 80%
“…(Further details on the technologists selected for blood sampling are shown in Appendix B.) We analyzed reciprocal chromosome translocations in two groups of radiologic technologists who provided blood samples in years 1994–1995 [Chromosome Translocation Study I (CTS-I), n = 90] and 2003 [Chromosome Translocation Study II (CTS-II), n = 152], as described previously (2225) with the current estimated occupational radiation doses (11) (Appendix A). [Note: the CTS-I (22) that previously assessed only 79 subjects, now includes 11 additional subjects for whom we did not previously have sufficient data to estimate doses.]…”
Section: Methodsmentioning
confidence: 99%
“…Studies of FISH translocation data in the Japanese A-bomb survivors (15) accounted for dosimetric uncertainties using regression-calibration methods (20). In general, this has not been attempted in populations with occupational radiation exposure (13, 2225), where complex patterns of shared errors (i.e., the component of dose error that is shared by a group of individuals in a study) and unshared errors (i.e., the component of dose error that is independent of the dose errors in other individuals) would be expected; or in populations where measurements of chemical or environmental exposures may not have been uniformly collected on individuals in the distant past. A distinction is often made between classical measurement error and Berkson error (20, 26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No relation was found between the age and gender, and frequency of CAs on the chromosomes, but some studies have indicated that the rate of CAs can be increased at the higher age (3,10). Moreover, the duration of exposure to radiation did not have any effect on the CAs.…”
Section: Discussionmentioning
confidence: 88%